Investigations on the inclusion of betulinic acid into CD-MOF-1 performed by Quantum Mechanics calculations and molecular docking simulation - Hisamuddin, Ahmad ‘Afifu’d-din; Saad, Hazizi Abu; Tejo, Bimo Ario; Mohammad Latif, Muhammad Alif; Tiofac, Saurelle Kenfack; Borzehandan, Mostafa Yousefzadeh; Tsobnang, Patrice Kenfack; Ahmad, Haslina; Ngoune, Jean (National University of Malaysia, 2025)
In recent years, CycloDextrin Metal-Organic Frameworks (CD-MOFs) have been investigated to develop potential drug carriers and improve the solubility of some molecules by their encapsulation. Betulinic acid (BA) or 3β-hydroxy-lup-20(29)-en-28-oic acid is a pentacyclic triterpene of the lupane family which has a wide range of biological activities, and it is considered a promising candidate for clinical application but, its high hydrophobicity and limited aqueous solubility contribute to its poor bioavailability. In this work, we show through computational studies that CD-MOF-1 can strongly encapsulate betulinic acid molecules through hydrogen bond interactions. For this purpose, the optimized geometry of BA was implemented by the Density Functional Theory using the function of Becke, Lee, Yang, and Parr (DFT/B3LYP) method with a 6-31+G(d) basis set using the Gaussian09 program and GaussView 5.0 for visualization. We noticed that BA has a lower energy gap (Egap = 6.1615 eV) indicating that it is soft, less stable, more reactive, and polarizable. According to the map of electrostatic potential (MEP), the active site of betulinic acid is the carboxylic group and the latter molecule preferred electrophilic attacks. The molecular docking was performed using AutoDock Vina v1.1.2 program and Discovery Studio Visualizer 16.1. The best binding affinities of BA and CD-MOF-1 had the lowest values of -8.2 KCal/mol and -11.5 KCal/mol for the simple and the packed CDMOF-1 structure respectively. The docking revealed that BA bound in the hydrophobic cavities of CD-MOF-1 through hydrogen bonds interactions which are [CD-MOF-1OH13···O28BA (2.95 Å)], [CD-MOF-1O13···H30BA (2.54 Å)], and [CD-MOF-1OH12···H30BA (2.12 Å)] for the simplest structure and [CD-MOF1OH12A···O28BA (3.00 Å)], [CD-MOF-1H13A···H30BA (2.72 Å)] and [CD-MOF-1OH2A···H30BA (2.66 Å)] for the packed structure 1×1×1. The packed CD-MOF-1 structure is the best with accurate results, this may be the factor of enhancement of betulinic acid solubility and bioavailability. The present theoretical results indicate the possibility of forming the host-guest inclusion complex between BA and CD-MOF-1 which may enhance the solubility of BA and then its efficiency for drug delivery.